2005
DOI: 10.1139/e04-065
|View full text |Cite
|
Sign up to set email alerts
|

Geology and U–Pb geochronology of the Neoarchean Snare River terrane: tracking evolving tectonic regimes and crustal growth mechanisms

Abstract: U–Pb zircon crystallization ages determined by isotope dilution – thermal ionization mass spectrometry (ID–TIMS) and laser ablation microprobe – inductively coupled plasma – mass spectrometry (LAM–ICP–MS) for 13 intrusive units in the Neoarchean Snare River terrane (SRT) provide tight constraints on the timing of crust formation and orogenic evolution. Seven metaluminous plutons were emplaced over ~80 Ma from ca. 2674 to 2589 Ma, whereas six peraluminous bodies were emplaced in a ~15 Ma interval from ca. 2598 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Seismic surveys (Cook et al 1999;van der Velden 2007) have shown that the Anton terrane (CSST) is a westward-tapering wedge-shaped indentor slicing through the Snare River terrane, which is interpreted to have sutured to the CSST (Anton terrane) at 2630-2620 Ma (Bennett et al 2005). Eastward-directed subduction of the Snare River terrane beneath the CSST preceding this collision is thought to be responsible for ca.…”
Section: Slave Cratonmentioning
confidence: 98%
“…Seismic surveys (Cook et al 1999;van der Velden 2007) have shown that the Anton terrane (CSST) is a westward-tapering wedge-shaped indentor slicing through the Snare River terrane, which is interpreted to have sutured to the CSST (Anton terrane) at 2630-2620 Ma (Bennett et al 2005). Eastward-directed subduction of the Snare River terrane beneath the CSST preceding this collision is thought to be responsible for ca.…”
Section: Slave Cratonmentioning
confidence: 98%
“…2.67e2.58 Ga Snare River terrane is composed of bimodal volcanic sequences, turbidite successions and synvolcanic plutons that are located in the southwestern portion of the Slave Province (Pehrsson and Villeneuve, 1999;Bennett et al, 2005). The Snare River domain is inferred to have collided with the Central Slave superterrane between 2.63 and 2.62 billion years ago (Pehrsson and Villeneuve, 1999;Bennett et al, 2005).…”
Section: Tectonic Evolution Of the Slave Provincementioning
confidence: 99%
“…Plutonic suites, linear greenstone belts, and a variety of sedimentary successions comprise the ca. 2.58e4.03 Ga (Bowring et al, 1989;van Breemen et al, 1992;Isachsen and Bowring, 1997;Bennett et al, 2005) Slave Province. Several features distinguish the Slave Province from most Archaean cratons, including a higher felsic/mafic volcanic rock ratio, more sedimentary than volcanic rocks, and abundant evolved potassium-rich granites (Henderson, 1981;Padgham and Fyson, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…These are clastic sedimentary rocks, dominantly greywackes, interpreted to be turbidite sequences. These rocks cover approximately 40% of the craton, ranging in metamorphic facies from greenschist to upper amphibolite with rare granulite occurrences, such as those in the Snare River area (Jackson, 2003 andBennett et al, 2005). There are three ages of sedimentation for the Yellowknife Supergroup: the >2680 Ma George Lake turbidites (van Breeman et al, 1992), the 2660-2680 Ma Burwash and equivalent formations and a younger formation dated at <2630 Ma, locally known as the Damoti formation in the Indin Lake area, but also found at Russell Lake (Pehrsson and Villeneuve, l999;Bennett et al, 2005;.…”
Section: Greenstone Belts and Meta-sedimentary Rocksmentioning
confidence: 99%
“…2680 Ma Cotterhill gneiss complex in the Indin Lake area (Pehrsson and Villeneuve, 1999) as well as the ca. 2680 to 2650 Ma trondjhemite-granodiorite-tonalite (TTG) plutons of the Snare River area (Bennett et al, 2005) are part of the pre-deformational granitoid group. The Anton Complex, once interpreted as part of the CSBC, is composed of 2630 to 2638 Ma foliated granodiorites and granites.…”
Section: Granitoid Rocksmentioning
confidence: 99%